2015
DOI: 10.1007/s11886-015-0628-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Intracranial Aneurysms: Clipping Versus Coiling

Abstract: Intracranial aneurysms (IAs) have an estimated incidence of up to 10 % and can lead to serious morbidity and mortality. Because of this, the natural history of IAs has been studied extensively, with rupture rates ranging from 0.5 to 7 %, depending on aneurysm characteristics. The spectrum of presentation of IAs ranges from incidental detection to devastating subarachnoid hemorrhage. Although the gold standard imaging technique is intra-arterial digital subtraction angiography, other modalities such as computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…47 Two well-conducted, randomized, controlled trials have evaluated these 2 methods in the treatment of intracranial aneurysms and looked at recurrence and retreatment rates. 7,66 In the International Subarachnoid Hemorrhage Trial (ISAT), 9.0% of patients treated with coiling and 0.85% of patients treated with microsurgical clipping had to be retreated due to recurrence.…”
Section: Previously Treated Aneurysmsmentioning
confidence: 99%
“…47 Two well-conducted, randomized, controlled trials have evaluated these 2 methods in the treatment of intracranial aneurysms and looked at recurrence and retreatment rates. 7,66 In the International Subarachnoid Hemorrhage Trial (ISAT), 9.0% of patients treated with coiling and 0.85% of patients treated with microsurgical clipping had to be retreated due to recurrence.…”
Section: Previously Treated Aneurysmsmentioning
confidence: 99%
“…Endovascular therapy is now the first-line treatment for the majority of cerebral aneurysms 1. However, aneurysm treatment after endovascular embolization has a higher frequency of recanalization than surgical clipping, ranging from 6.1% to 33.6% 2.…”
Section: Introductionmentioning
confidence: 99%
“…Although coil embolization is superior compared with surgical clipping when considering the physical burden on patients, aneurysmal recanalization and re-treatment remain major problems for this method. 1–6 In previous studies, recanalization was observed during follow-up in approximately 10% to 25% of coil-embolized aneurysms. 7 8 Many attempts have been made to overcome the drawbacks of coil embolization, including the development of parameters that can help predict recanalization or re-treatment.…”
Section: Introductionmentioning
confidence: 91%